The Utility of Thiopurine Methyltransferase Enzyme Testing in Inflammatory Bowel Disease - Laura Chisick; Curtis Oleschuk; Charles N Bernstein (Canadian Journal of Gastroenterology)
OBJECTIVE: To assess the levels of red blood cell thiopurine methyltransferase (TPMT) in subjects with inflammatory bowel disease (IBD) and to determine how these levels impacted thiopurine dosing and leukopenia over the first six months of therapy.